Influence of weather parameters on the seasonal incidence of sucking pests of pomegranate, Punica granatum L. during ambia bahar (Indian Journal of Arid Horticulture, 2024)
The pomegranate, Punica granatum L. (Family: meteorological week with corresponding weather Punicaceae) is a favourite table fruit in the tropical and parameters viz., maximum and minimum temperature,  subtropical region of the world. The successful cultivation morning and evening relative humidity, sunshine period and  and effective utilization of this fruit crop depends upon the rainfall were 29.57 and 13.54 C, 65.29 and 30.86 per cent.
Keywords: Karruppuchamy; Meteorologi; humidity